Globalization and international business cycle dynamics a conditional GVAR approach - Binder, Michael 1967-; Offermanns, Christian J. 1975- (Freie Univ. Berlin, FB Wirtschaftswiss., 2014)
We examine the effects of increased international integration of both goods and financial markets on business cycle dynamics. To do so, we develop a new econometric framework for modelling cross-country spillovers in which the magnitude of these spillovers is an empirically determined function of the degree of a country's integration with international goods and financial markets. Our results suggest that the magnitude of cross-country spillovers for most country pairs has been increasing with strengthened goods and financial markets integration.
Keywords: Globalisierung; Konjunktur; Panelanalyse; Wirtschaftliche Integration; Kreditmarkt; Gütermarkt